CURRENT TRENDS IN THE FORMATION OF MARKETING STRATEGY OF TRADE ENTERPRISES - MIZINA, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The main scientific goal of this work is to study modern trends in the formation of marketing strategies in the context of the development of e-commerce and Internet communications and to determine the key determinants of this process. Consideration of the theoretical foundations of the formation of marketing strategies in the aspect of modernity has shown that there are new requirements for the formation of enterprise strategies, including functional ones. The approach in which strategic marketing planning is limited to defining a future-oriented overall direction of operations is changing. The emphasis is shifting towards the formation of an efficient market-oriented system with an appropriate allocation of the firm’s resources. The marketing strategy should contain a set of measures to strengthen the competitive position in the target market, and today’s reality is such that it is almost impossible without promoting the company on the Internet. Moreover, today the issue of transition to integrated marketing communications is relevant, and the complex of Internet communications is precisely those new modern tools that can complement and strengthen the classic set of five basic tools (advertising, sales promotion, etc.). A study was conducted on the possibilities and feasibility of using Internet tools and relevant information and communication technologies in the field of market research, product promotion, and effective use of resources. On the example of one of the most competitive niches in the field of e-commerce (sales of electronics and household appliances), a study of key trends in online sales of Ukrainian online stores was carried out, directions for developing an online promotion strategy were determined, based on the goals and restrictions of the market. From a modern point of view, the individual elements of the marketing complex, their semantic content are considered, an assessment of the strengths and weaknesses of various Internet communication channels is presented, which makes it possible to design their growth zones within the framework of solving problems and achieving the goals of specific market entities.